Uffizi, Florence. - ragghianti,carlo ludovico; Dalli Regoli, Gigetta (New York : Newsweek,INC., 1968)
The treasures of the Uffizi Gallery in 142 photographs, all reproduced in full color. Includes descriptions of the works.
italy, flanders,germany, france history of the collection,the building.
including index.
Bibliography: p. 168.
Includes indexes.
All age.
Keywords: Dalli Regoli, Gigette; Galleria degli Uffizi; Painting -- Italy -- Florence -- Catalogs